(untitled) (Research, Society and Development, 2021)
The inoculation of growth-promoting bacteria has already shown benefits in different cultures such as increased biomass production for the growth of roots and stems, greater resistance to water stress conditions and changes in their physiological properties. Plant growth promoting bacteria have stood out for their potential application in plant production, allowing the reduction of the use of fertilizers and pesticides, which is due to the ability to stimulate the growth of plants by biological means by nitrogen fixation and production of phytohormones , such as indole-3-acetic acid (IAA). The aim of this study was to verify the potential for promoting plant growth of 25 wild bacteria from the Agricultural Microbiology Culture Collection at the Federal University of Lavras (CCMA-UFLA) by assessing the capacity for biological nitrogen fixation and IAA production; select growth-promoting bacteria, in addition to evaluating the effect of 3 isolates on seedlings of Musa sp. grown in vitro. The experiment was conducted in a completely randomized design (CRD), containing 3 treatments, plus the control, with 30 explants per treatment. The bacterium CCMA0056 caused the death of all seedlings in vitro. Banana growth is reduced when inoculated with the bacteria Azospirillum brasilense and Enterobacter cloacae.